EFFICACY OF DIPEPTIDYL PEPTIDASE-4 INHIBITORS THERAPY IN DIFFERENT POPULATIONS - Iskakova, A.N.; Zholdybayeva , E.V. (Eurasian Journal of Applied Biotechnology, 2016)
Introduction. Different drug classes in addition to lifestyle adjustments are used to reduce glucose level. Class of dipeptidyl peptidase-4(DPP4) inhibitors is one of them. The aim of our study was to compare the glucose-lowering efficacy of DPP4 inhibitors among different populations. Methods. MEDLINE database has been searched. Randomized controlled trials were included in the analysis if there were comparison of DPP4 inhibitors vs. placebo in a form of monotherapy or combination therapy with treatment duration of at least 12 weeks. Other criteria were information on ethnicity, baseline glycated hemoglobin (HbA1c) levels, fasting plasma glucose (FPG) levels and its levels after therapy, or HbA1c and FPG data compared to the baseline. Results. Of the 527 publications identified from the databases, 22 studies were included in the analysis. The difference between "Japan", "China", "Korea" and "Europe" subgroups was -0.84% ​​(95% CI -1.07, -0.62; I2 = 65.2%) which was statistically significant (p<0.05). The FPG value difference between the subgroups was -1.07 mmol/L (95% CI -1.26, -0.87; I2 = 83.6%) with a statistically significant probability (p <0.05). Conclusion. HbA1c-lowering efficacy of DPP4 inhibitors is higher in the Japanese population than in Korean, while FPG-lowering efficacy higher in the Korean population when compared to the Japanese and Chinese populations.